Mastication stimuli enhance the learning ability of weaning-stage rats, altering the hippocampal neuron transcriptome and micromorphology - Yasuoka, Akihito; Nagai, Toshitada; Lee, Seonmi; Miyaguchi, Hitonari; Saito, Yoshikazu; Abe, Keiko; Asakura, Tomiko (Frontiers in Behavioral Neuroscience, 2022)
Mastication stimuli are known to relieve senile dementia in human and animal studies. However, few studies have focused on its effect on weaning-stage animals and the underlying molecular processes. In this study, 3-week-old male rats were raised on a powdered (P-group) or chow (C-group) diet for 8 days, and their behavior was examined using the Y-maze and novel object recognition tests. In the Y-maze test, the C-group rats showed a larger alternation ratio than the P-group rats. In the novel object recognition test, the C-group rats exhibited a significantly larger discrimination index for novel objects than for familiar objects, but the P-group rats did not. We then compared the hippocampal neuron morphology and transcriptome between the groups. C-group rats exhibited larger dendrite branch numbers in the apical dendrites of pyramidal cells in the cornu ammonis 1 (CA1) region and a larger spine density in the basal dendrites of CA1 neurons than the P-group rats. Using DNA microarray analysis, we identified 621 (P < C) and 96 (P > C) genes that were differentially expressed between the groups. These genes were enriched in functional terms related to dendrite growth and included the Igf2, RhoA, and Rho GEF genes, most of which were upregulated in the C-group. These results suggest that the mastication stimuli during the weaning period can enhance the learning ability of rats by increasing the dendrite branches of hippocampal CA1 neurons and by regulating genes related to dendrite growth.